Pengaruh Risiko Kredit Dan Risiko Operasional Terhadap Kinerja Keuangan Pada PT. Bank Papua Kantor Cabang Utama (KCU) Manokwari - Devi Kurniasti; Martinus Budiantara (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the financial performance of PT. Bank Papua Kantor Cabang Utama (KCU) Manokwariwhich is affected by Credit Risk and Operational Risk. This study used a quantitative approach with data collection usingsecondary data. The type of data used in this study used panel data. The population in this study is the financialstatements of PT. Bank Papua KCU Manokwari. The sampling technique used is purposive sampling. The data analysis technique used in this study uses descriptive statistical analysis and classical assumption test analysis to examine the effect of more than one independent variable on the dependent variable. Credit Risk (NPL) has an effect and is significant on financial performance (ROA), Operational Risk (BOPO) has an effect and is significant on financial performance and Credit Risk and operational risk Credit Risk and Operational Risk have a significant effect simultaneously on financialperformance. Keywords : Credit Risk, Operational Risk, Financial Performance, NPL,BOPO,ROA